Gender and the Building Up of Many ‘Peaces’: A Decolonial Perspective from Colombia dans Gender, conflict, peace, and UNSC resolution 1325 - Anctil Avoine, Priscyll; Tillman, Rachel; Mejía Jerez, Yuly Andrea (Gender, conflict, peace, and UNSC resolution 1325, 2018)
As we write this chapter about reinterpreting women’s roles in peacebuilding, Colombia is at a turning point. On November 24, 2016, the Revolutionary Armed Forces of Colombia—People’s Army (FARC-EP) and the national government signed a historical agreement that ended the 60-year-long armed conflict. How this peace and the social reconciliation that it requires will be implemented remain to be seen. At the peace negotiations roundtable, throughout the early years of the conversations, women were underrepresented, and even now gender inequality within public participation is far from being resolved. Although women have been acting equally with their male counterparts as rotating negotiators in these peace negotiations, the High Commissioner for Peace (Alto Comisionado para la Paz) affirms that only 25 percent of the plenipotentiary negotiators are women, and that while the Gender Subcommittee is an interesting accomplishment, it is still insufficient. Additionally, Colombia is facing the challenge of FARC-EP’s reintegration to civil society: between 33 percent and 40 percent of their troops are women and most of the DDR processes do not show a serious focus on gender in their programs.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique latine; amériques; approches et analyses; colombie; corps; cours; discipline; féminisme décolonial; pol4022; premier cycle; périodes historiques; racisme; régions géographiques; science politique; système colonial; systèmes d'oppressions; thématiques; violences

Keetsahnak: our missing and murdered Indigenous sisters - Anderson, Kim; Campbell, Maria; Belcourt, Christi (The University of Alberta Press, 2018)
«In Keetsahnak / Our Murdered and Missing Indigenous Sisters, the tension between personal, political, and public action is brought home starkly. This important collective volume both witnesses the significance of the travelling exhibition Walking With Our Sisters and creates a model for antiviolence work from an Indigenous perspective. The contributors look at the roots of violence and how it diminishes life for all. They acknowledge the destruction wrought by colonial violence, and also look at controversial topics such as lateral violence, challenges in working with "tradition," and problematic notions involved in "helping." Through stories of resilience, resistance, and activism, the editors give voice to powerful personal testimony and allow for the creation of knowledge.»-- Provided by publisher.
Keywords: activisme; amériques; anti-violence; approches et analyses; canada; cours; droits des femmes*; droits des femmes* autochtones; féminicide; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; régions géographiques; résistance; système colonial; systèmes d'oppressions; thématiques; violences

Concrete Ways to Decolonize Research - Asselin, Hugo; Basile, Suzie (An International Journal of Critical Geographies, 2018)
« Almost 20 years after Māori scholar Linda Tuhiwai Smith’s call to decolonize research (Smith, 1999), significant progress has been made into drafting ethics principles to guide research with Indigenous people (e.g., CIHR et al., 2014). However, transforming principles into actual practices is easier said than done. It is increasingly recognizedthat “knowing the key guiding principles for research with Indigenous peoples is not always enough and [principles need to be]translated into day-to-day research practices”(Morton Ninomiya and Pollock, 2017, p. 29). This themed issue presents studies on various topics conducted in different geographical and cultural settings and suggesting concrete ways to decolonize research. The call for papers was issued following the 3rd Seminar on the ethics of research with Aboriginal people held at the Université du Québec en Abitibi-Témiscamingue in late 2014. Two previous editions of the seminar (in 2009 and 2011) had invitedparticipants2to share experiences of good and bad research practices, summarized in Asselin and Basile (2012). The 3rd seminar took a step further in focusing on concrete ways to decolonize research.In what follows, we discuss research decolonization and summarize the key messages from the keynote speakers of the 3rd seminar, some of which have contributed papers to this themed issue. Additional contributions widened the geographical scope considered (Canada, Mexico, Peru) in addition to providingmore examples of concrete ways to decolonize research. » [Extrait original p. 643-644|
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; autochtones; canada; décolonialisme; justice sociale; orpcc; outils; pour des recherches en milieux de pratiques; premiers peuples; périodes historiques; recherche en milieux de pratique; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions

LA PARTICIPATION DES FEMMES AUX LUTTES ARMÉES Pour un renouvellement des approches de l’acteur combattant - Boutron, Camille (Institut de Recherche Stratégique de l'Ecole Militaire, 2018)
Cette note de recherche propose de nouvelles pistes de réflexion sur l’expérience combattante féminine. Se focalisant sur la participation des femmes aux groupes armés non étatiques après la Seconde Guerre mondiale et s’intéressant plus particulièrement à l’expérience latino-américaine, elle traite deux aspects du sujet. D’une part, elle formule l’hypothèse d’une émancipation par les armes, étudie les ressorts de l’engagement des femmes au sein des insurrections armées dans un contexte de décomposition des empires coloniaux et d’émergence de mouvements de « libération nationale », et montre que cette participation féminine est influencée par l’émergence des théories féministes pendant la même période. D’autre part, elle examine les conséquences de l’engagement des femmes dans les conflits armés sur l’ensemble de leur trajectoire de vie en posant la question de leur réinsertion dans la vie civile. La sortie de conflit s’accompagne généralement d’une injonction faite aux femmes combattantes de retrouver leur rôle traditionnel au sein de la sphère domestique. La note met enfin en relation l’analyse de l’expérience combattante féminine et l’étude des conflits armés contemporains.
Keywords: 1900-1999; 1950-1959; 1960-1969; amérique latine; amériques; approches et analyses; corps; cours; discipline; féminisme décolonial; pol4022; premier cycle; périodes historiques; régions géographiques; science politique; système colonial; systèmes d'oppressions; thématiques; violences

Whose Land Is It Anyway?: a Manual for Decolonization - McFarlane, Peter; Schabus, Nicole (Federation of Post-Secondary Educators of BC, 2018)
We are pleased to announce the publication of Whose Land Is It Anyway? A Manual for Decolonization; inspired by a 2016 speaking tour by Arthur Manuel, less than a year before his untimely passing in January 2017. The book contains two essays from Manuel, described as the Nelson Mandela of Canada, and essays from renowned Indigenous writers Taiaiake Alfred, Glen Coulthard, Russell Diabo, Beverly Jacobs, Melina Laboucan-Massimo, Kanahus Manuel, Jeffrey McNeil-Seymour, Pamela Palmater, Shiri Pasternak, Nicole Schabus, Senator Murray Sinclair, and Sharon Venne. FPSE is honoured to support this publication.
Keywords: amériques; approches et analyses; canada; cours; féminisme décolonial; histoire et politique; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Danser sur le dos de notre tortue = Niimtoowaad mikinaag gijiying bakonaan: nouvelle émergence des Nishnaabeg - Simpson, Leanne Betasamosake; Régimbald, Anne-Marie (Collection Proses de combat, 2018)
"On parle beaucoup au Québec, comme dans le reste du Canada, de réconciliation avec les Premières Nations. Mais pour qu'un rapprochement fécond puisse avoir lieu, qu'une nouvelle ère, égalitaire et respectueuse, s'ouvre, le cadre constitutionnel canadien ne peut à lui seul en définir les règles. Toute entente devra aussi tenir compte des traditions autochtones. C'est dans ce contexte que le livre de Leanne Simpson trouve toute sa pertinence. L'auteure s'y demande comment redonner force, consistance et valeur à un héritage politique, juridique et culturel mis à mal par le processus colonial. D'une façon aussi concrète que tonique et audacieuse, elle y explore la langue, les mythes, les coutumes et les expériences de sa culture ancestrale afin de recouvrer et révéler cette manière singulière et originale d'être au monde trop longtemps méprisée. Si l'entreprise est inspirante pour toute communauté issue des Premières Nations, elle l'est également pour quiconque s'intéresse aux contradictions de la modernité occidentale."-- Renaud-Bray.
Keywords: amériques; approches et analyses; arts; canada; cours; discipline; féminisme autochtone; histoire et politique; lit3495; militance; ojibwa; premier cycle; premières nations; québec; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences; études littéraires

Apprentissages croisés 1 : Introduction - Stinson, Jane (Institut canadien de recherches sur les femmes, 2018)
« Ce premier feuillet d’info de la série « Apprentissages croisés des systèmes de connaissances autochtones et occidentaux et l’intersectionnalité » sert d’introduction à l’approche de recherche, aux principales considérations et utilisations de ce travail. Ces feuillets d’information survolent certains éléments des modes de savoirs autochtones et occidentaux. Ils explorent les liens potentiels entre approches autochtones et occidentales en matière de création de savoirs, fournissent des exemples et identifient les risques. En outre, les feuillets d’information présentent et explorent l’intersectionnalité en tant qu’important concept complémentaire pouvant renforcer l’analyse et appuyer le travail de vérité et de réconciliation. Sept grands principes visent à orienter les universitaires, les décisionnaires politiques et toute autre personne intéressée à mener une recherche à l’écoute de la réconciliation par l’entremise de l’intersectionnalité. Enfin, douze méthodes sont illustrées par des exemples démontrant comment mener des recherches reliant des modes de savoirs autochtones et occidentaux et l’intersectionnalité » [Résumé original]
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; autochtones; canada; intersectionnalité; orpcc; outils; pour des recherches en milieux de pratiques; premiers peuples; périodes historiques; recherche en milieux de pratique; recherche partenariale; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques

Apprentissages croisés 2 : Quels sont les modes de savoirs autochtones et occidentaux ? - Stinson, Jane (Institut canadien de recherches sur les femmes, 2018)
« Ce deuxième feuillet d’info de la série « Apprentissages croisés des systèmes de connaissances autochtones et occidentaux et l’intersectionnalité » présente les fondements dans le cadre de la transposition des perspectives autochtones et occidentales. Toutefois, il n’existe pas de mode unique de savoirs autochtones ou occidentaux et donc on doit éviter de réduire des traditions vastes et variées à des termes simplistes et généraux. On souligne les risques que comporte l’intégration de ces visions du monde et on explore les cadres de recherche qui réunissent les perspectives autochtones et occidentales à la création de savoirs » [Résumé original]
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; autochtones; canada; orpcc; outils; pour des recherches en milieux de pratiques; premiers peuples; périodes historiques; recherche collaborative; recherche en milieux de pratique; ressource en ligne; régions géographiques; savoirs; système colonial; systèmes d'oppressions; thématiques

Climate change, colonialism, and women’s well-being in Canada: What is to be done? - Williams, Lewis (Canadian Journal of Public Health, 2018)
The impacts of accelerating climate change across Canada are unequally distributed between populations and regions. Emerging evidence shows climate change and resultant policies to be worsening gendered social and economic inequities between women and men, with women’s participation largely absent in climate change research and decision-making. These dynamics are resulting in negative impacts for women’s well-being, with Indigenous and historically marginalized women at increased risk of experiencing health inequities as a result of climate change. To date, public health discourse has largely failed to incorporate gender as a key determinant of health in discussions of climate change impacts on populations. Paralleling this lack of development, the entangled relationship between climate and colonialism tends to be subsumed under the term “Aboriginality” within health determinants discourse. This commentary on gender and climate change in Canada is framed within a radical intersectional approach as an alternative course of public health analysis and action aimed at addressing resulting health and power inequities. Following an overview of evidence regarding the gendered impacts of climate change on women’s work, roles, agency, and well-being, several possible public health action areas on climate change and gender are highlighted as necessary components for resilient communities capable of meeting contemporary challenges.
Keywords: amériques; approches et analyses; canada; changements climatiques; environnement; intersectionnalité; invisibilisation des femmes autochtones; projet charge mentale; régions géographiques; santé; santé des femmes*; sexisme; système colonial; systèmes d'oppressions; thématiques